Performance Evaluation of Different Octane Numbers on Toyota Yaris Through Dynamometer Test and Engine Simulation - fadhlan nazhif iskandar; rahmat nur adi wijaya; sentot wahjoe goeritno (Liaison Journal of Engineering, 2023)
On April 1st 2022, fuel prices in Indonesia including PT Pertamina’s non-subsidized Pertamax RON 92 and Pertamax Turbo RON 98 fuels rose by up to 39% while the price of the subsidized Pertalite RON 90 fuel remained constant. The escalation of price differences appeared to sway the non-subsidized fuel consumer’s preference to switch to the much cheaper subsidized fuel with lower Research Octane Number (RON), thus resulted in a market shift to the Pertalite RON 90 fuel, which fuel octane rating is lower than the requirement and recommendation from the car manufacturer, the government, and the fuel supplier. The purpose of the study is to compare, analyze and evaluate performance differences such as torque, power and specific fuel consumption when using different octane number of fuels including Pertalite, Pertamax and Pertamax Turbo on a 2015 Toyota Yaris with 1NZ-FE engine through dynamometer test and engine modeling simulation. The result from the dynamometer test revealed that using Pertalite RON 90 decreased the torque, power, and specific fuel consumption in average by 3.85%, 3.83% and 9.58% respectively, while using Pertamax Turbo RON 98 only increased the numbers by 2.3%, 2.31% and 13.43% respectively, both compared to when using Pertamax RON 92. The result from the engine modeling simulation also revealed similar trend, where using Pertalite RON 90 decreased the torque, power, and specific fuel consumption in average per cylinder by 1.22%, 1.21% and 1.22% respectively, while using Pertamax Turbo RON 98 only increased the numbers by 1.02%, 1.01% and 0.99% respectively, both also compared to when using Pertamax RON 92. The results illustrated the increase in performance when using higher RON, but the performance gain from Pertamax RON 92 to Pertamax Turbo RON 98 is smaller than the gain from Pertalite RON 90 to Pertamax RON 92. Keywords: Engine Performance; Research Octane Number; Pertalite RON 90; Pertamax RON 92; Pertamax Turbo RON 98; Torque; Power; Specific Fuel Consumption